Widerstandsmomente - Schmeiser, Jo 1967-; Maintigneux, Sophie 1961- (sixpackfilm, 2019)
"Widerstandsmomente (Moments of Resistance) carries voices, writings and objects from the anti-Nazi resistance into the present. Politically engaged women of today respond to historical resistance and make links to current events. A line is drawn from what was before and what is today to what might be: a society based on solidarity without discrimination or exclusion." [imdb.com]
Original: Deutschland, Österreich 2019
Keywords: Widerstand; Frau; Film; DVD-Video